Technically yours - Williams, Denise, 1982- (Berkley Romance, 2023)
"Pearl Harris has learned the hard way to be careful in work and in love. When she is appointed acting director of OurCode, a nonprofit aimed at inspiring high schoolers to code, she has a chance to make lasting change for the organization, but a scandal has put their reputation at risk. Further complicating matters, Pearl didn't expect the one man she hasn't stopped thinking about in seven years to be the newest member of her board of directors. Cord Matthews fell for Pearl when they met in an elevator seven years ago. She's just his type: smart, capable, and makes him laugh, but when she broke his heart, he decided love wasn't for him. After five years with no contact, their connection is immediate despite the many roadblocks in their way and Cord must consider breaking his ban on serious relationships. But going public with a romance between them might derail Pearl's career and the progress she's made at OurCode. Pearl and Cord both are hesitant to trust their feelings and take a risk as they grow closer, but it becomes impossible to keep ignoring the electricity between them. Cord is a skilled programmer, but a workplace romance might spell disaster for both of them, and love isn't easily debugged"--